KINERJA PENYULUH PERTANIAN DI KABUPATEN KONAWE - La Ode Kimon; Salahuddin; Nurhayu Malik; Sitti Nur Isnian (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2024)
This study aims to analyze the performance of extension workers in agricultural extension in Konawe Regency. The research was conducted in Konawe Regency, Southeast Sulawesi Province. The location of this research was determined purposively or intentionally. The study population consisted of all agricultural extension workers employed by the State Civil Apparatus (ASN) in Konawe Regency, amounting to 113 individuals (a saturated sample/census). The research variable was the performance of extension workers in agricultural extension in Konawe Regency, encompassing their performance in planning, implementing, evaluating, and reporting extension activities. The data analysis was conducted to describe the state of the variable performance of extension workers in agricultural extension. Descriptive statistics with the interval formula were employed. The results indicated that the performance of extension workers in agricultural extension in Konawe Regency was in the medium category. Agricultural extension workers in Konawe Regency exhibited satisfactory performance in agricultural extension; however, there is a need for improvement to achieve high or very good performance in agricultural extension in Konawe Regency.